Analisis Implementasi Kurikulum Berbasis Kompetensi Pada Program Champion Class di SMAS Sabilillah Sampang - Mahrus Sholihin; Badruttamam Badruttamam (AL -ALLAM, 2026)
In facing the challenges of 21st-century education, a competency-based curriculum is an important approach to producing graduates who not only excel academically but also possess critical, creative, collaborative, and communicative thinking skills. Sabilillah Senior High School, Sampang, responds to this demand through the Champion Class Program, a flagship program aimed at fostering high-achieving students in both academic and non-academic fields. This program uses a more intensive, competitive learning model, and is oriented towards holistic competency achievement. This study aims to answer two main questions: First, how is the implementation of the competency-based curriculum in the Champion Class Program at Sabilillah Senior High School, Sampang? Second, what are the challenges of implementing this curriculum on student academic and non-academic achievement? This study uses a qualitative approach with a case study type. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Informants consisted of the principal, vice principal for curriculum, Champion Class mentor teachers, and students participating in the program. Data validity was tested through triangulation of sources and techniques, as well as in-depth observation. The results of the study indicate that: First, the implementation of the competency-based curriculum was carried out in stages and systematically, starting with the joint planning stage between the principal, the vice-curriculum director, and senior teachers, developing a learning roadmap, and continuing with regular implementation and evaluation. Learning in the Champion Class is designed to be project- and competition-based, with an emphasis on critical thinking skills, collaboration, leadership, and strengthening Islamic character. Second, challenges faced in implementing this program include: limited supporting facilities and infrastructure, varying levels of teacher understanding of the competency-based curriculum concept, and resistance from some parents and students to the new system. Despite this, the Champion Class has proven successful in achieving success in various competitions at the district and national levels, such as science olympiads and English competitions. Strong school management support, intensive teacher training, and the involvement of mentors are key to the program's success.